Pulse Radiolysis Study of Catalytic Properties of Human Manganese Superoxide Dismutase: A Review - Alhassan A. J.*, Muhammad, I. U., Sule, M.S, Adamu, S.M. and Umar, Y. (Sokoto Journal of Medical Laboratory Science)
The depletion of superoxide catalyzed by human manganese superoxide dismutase (MnSOD) was observed spectrophotometrically by measuring the absorbance of superoxide at 250-280 nm following pulse radiolysis and it showed a biphasic pattern. Tryptophan 161 is a highly conserved residue that forms a hydrophobic side of the active site cavity of manganese superoxide dismutase (MnSOD), with its indole ring adjacent to and about 5 Å from the manganese. Trp 161 promotes the dissociation of product peroxide, perhaps in part through its effect on the orientation of Tyr 34.